Improvement Strategy Quality Public Services in the Organizational Section District Regional Secretariat - Gusliana, Yeni; Zulher, Zulher; Kasmawati, Kasmawati (Dinasti Publisher, 2026)
This study aims to analyze strategies for improving the quality of public services in the Organizational Section of the Kampar Regency Regional Secretariat. The background of the study is based on the importance of public services as an indicator of government performance, as well as the ongoing obstacles in its implementation even though the Public Satisfaction Index (IKM) shows an increasing trend. This study uses a qualitative approach with descriptive methods. Data were obtained through observation, interviews, and documentation, then analyzed using the SWOT approach to identify internal and external organizational factors. The results show that the quality of public services has improved, but is not yet fully optimal. The main obstacles include the inconsistent implementation of standard operating procedures, limited competency of apparatus, and the suboptimal use of technology. Based on the SWOT analysis, strategies that can be implemented include increasing human resource capacity, utilizing information technology, and simplifying service procedures. This study concludes that improving the quality of public services requires integrated and sustainable efforts to be able to meet the needs and expectations of the community more effectively.